Maintenance Therapy for Inflammatory Bowel Disease: What Really Works - Lloyd R Sutherland (Canadian Journal of Gastroenterology)
The propensity of inflammatory bowel disease sufferers to experience recurrent episodes or disease flares is well documented. Until a cure can be found, strategies to lengthen the period of remission offer the greatest opportunity to reduce morbidity and enhance patient quality of life. Therapies that have been shown in randomized, controlled, double-blind clinical trials to either lengthen the time of remission or improve the odds of staying in remission during a set time interval are required.